Analysis of HIV type 1 gp41 and enfuvirtide susceptibility among men in the United States who were HIV infected prior to availability of HIV entry inhibitors. - Hudelson, Sarah E; Marlowe, Natalia; Huang, Wei; Bruce, Robert; Church, Jessica D; Husnik, Marla; Donnell, Deborah; Coates, Thomas; Jackson, J Brooks; Chesney, Margaret; Koblin, Beryl; Eshleman, Susan H (AIDS research and human retroviruses, 2009)
We analyzed HIV gp41 from 195 men in the United States who were HIV-1 infected between 1999 and 2002, before enfuvirtide (ENF) was approved for clinical use in the United States. gp41 genotyping results were obtained for 175 samples. None of the samples had major ENF resistance mutations. Six (3.4%) samples had minor ENF resistance mutations in the HR1 region (V38G, N43K, L44M, L45M). Twenty-eight (16%) samples had the N42S polymorphism, which is associated with ENF hypersusceptibility. Accessory mutations in the HR2 region were identified in some samples (E137K, S138A). Five of the six samples with HR1 resistance mutations were analyzed with a phenotypic assay; one sample had reduced ENF susceptibility (a sample with N42S +L44M + E137K). Prior to the availability of ENF, some men in the United States were infected with HIV that contained mutations associated with ENF resistance or hypersusceptibility. However, most of the mutations were not associated with phenotypic ENF resistance.
Keywords: Amino Acid Substitution; Drug Resistance, Viral; HIV Envelope Protein gp41; HIV Fusion Inhibitors; HIV Infections; HIV-1; Humans; Male; Peptide Fragments; Polymorphism, Genetic; RNA, Viral; Sequence Analysis, DNA; Time Factors; United States